2019
DOI: 10.1021/acsphotonics.8b01583
|View full text |Cite
|
Sign up to set email alerts
|

A Planar Scanning Probe Microscope

Abstract: Scanning probe microscopy (SPM) is traditionally based on very sharp tips, where the small size of the apex is critical for resolution. This paradigm is about to shift, since a novel generation of planar probes (color centers in diamond 1 , superconducting sensors 2 and single electron transistors 3 ) promises to image small electric and magnetic fields with hitherto inaccessible sensitivity. To date, much effort has been put into fabricating these planar sensors on tip-like structures. This compromises perfor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 30 publications
0
9
0
1
Order By: Relevance
“…The NV layer is first moved into focus, then the sample is brought up until it is seen to contact the diamond through the NV PL video feed (sample features come into focus, and the sample is stabilized when the diamond comes into contact). Compared with the method of Ernst et al 23 , this method is manual and does not allow estimation of the actual standoff directly.…”
Section: (C)]mentioning
confidence: 99%
See 2 more Smart Citations
“…The NV layer is first moved into focus, then the sample is brought up until it is seen to contact the diamond through the NV PL video feed (sample features come into focus, and the sample is stabilized when the diamond comes into contact). Compared with the method of Ernst et al 23 , this method is manual and does not allow estimation of the actual standoff directly.…”
Section: (C)]mentioning
confidence: 99%
“…Overcoming standoff limitations will require finer angular and vertical control of the probe, easily accomplished using robotic stages 23 . Keeping the surfaces clean and flat to further reduce d SO should be readily achiev- able.…”
Section: (C)]mentioning
confidence: 99%
See 1 more Smart Citation
“…In an alternative approach, the sample is attached to the cantilever of a commercial scanning probe microscope and scanned over an NV embedded ≈ 5 nm below an SCD surface and is equivalent to scanning of diamond probes over the sample surface [ 61 , 62 ]. Ernst et al [ 63 ] recently demonstrated another method of using planar SCD (50 µm thick) with single NV centers as scanning probes for imaging planar samples, which required highly precise alignment (radial) and proximity control between sensor and sample. While initial scanning probes relied on grafting color center containing diamond nanocrystals to AFM tips, the focus recently shifted to realization of top-down fabricated SCD nanoprobes [ 20 , 60 ].…”
Section: Photonic Componentsmentioning
confidence: 99%
“…46,47) Die Gruppe Reinhard veröffentlichte Arbeiten zum Planar-Scanning-Probe-Mikroskop, das sowohl den Winkel als auch den Abstand zur Probe mit einer Präzision von Submillirad und Subnanometer bestimmt. 48) Spektrometerentwicklung und Miniaturisierung pe ri men te 59) eignet. Mit einem solchen Spektrometer führten Akhtar und Coautoren gepulste Elec trical-De tected-Mag netic-Re sonance (ED MR)-Experimente zum spinabhängigen Transport an Solarzellen in Betrieb durch, wodurch sie temperaturabhängige Hopping-und Rekombinationsprozesse nachgewiesen haben.…”
unclassified